Rancang Bangun Robot Pelontar Shuttlecock - Rodika Rodika; Jamalludin Jamalludin; Handriko Handriko; Aryono Priyambudi; Aldi Pranata (Manutech : Jurnal Teknologi Manufaktur, 2017)
The design of robot launcher shuttlecock is done by researchers so that the robot produced can help human activity in the field of sports. This throwing robot can be used as a training medium for selftaught players, where practice can be done without a trainer / helpers. Players can practice at any time without being linked with others (trainers / feeders) so that training time can be maximized. The methodology of this tool includes the manufacture and design of hardware and software. The manufacture and design of mechanical hardware involves the construction of aluminum frames, with actuators in the form of motors and pneumatic systems while for the design and manufacture of electronics hardware includes the manufacture of control circuits. Preparation and design of software include programming mikrokontroler ATMega128. From the test results, the robot can throw shuttlecock. Robot can do 6 mode service ie service mode near, far, left, right, random and join with average success percentage equal to 93,35%.